Exploring Acetogenesis in Firmicutes: From Phylogenetic Analysis to Solid Medium Cultivation with Solid-Phase Electrochemical Isolation Equipments - Zen-ichiro Kimura; Hiroki Kuriyama; Yuki Iwasaki (Microorganisms, 2023)
This study introduces a groundbreaking approach for the exploration and utilization of electrotrophic acetogens, essential for advancing microbial electrosynthesis systems (MES). Our initial focus was the development of Solid-Phase Electrochemical Isolation Equipment (SPECIEs), a novel cultivation method for isolating electrotrophic acetogens directly from environmental samples on a solid medium. SPECIEs uses electrotrophy as a selection pressure, successfully overcoming the traditional cultivation method limitations and enabling the cultivation of diverse microbial communities with enhanced specificity towards acetogens. Following the establishment of SPECIEs, we conducted a genome-based phylogenetic analysis using the Genome Taxonomy Database (GTDB) to identify potential electrotrophic acetogens within the Firmicutes phylum and its related lineages. Subsequently, we validated the electrotrophic capabilities of selected strains under electrode-oxidizing conditions in a liquid medium. This sequential approach, integrating innovative cultivation techniques with detailed phylogenetic analysis, paves the way for further advances in microbial cultivation and the identification of new biocatalysts for sustainable energy applications.